2004
DOI: 10.1111/j.1095-8312.2004.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of how frogs jump out of water

Abstract: Euphlyctis cyanophlyctis and E. hexadactylus are two common frog species from south-east Asia. Both species have the remarkable ability to leap from a floating position out of the water. Rana esculenta is a European species from the same family that barely manages to do so. The species' morphology, however, looks roughly the same. We studied the unique abilities of the Euphlyctis species by videotaping the three species mentioned above whilst they jumped out of the water. These recordings enabled us to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The generation of thrust is possible because of the viscosity of water relative to body size; the paddles and spurs act in a similar way to the smaller hairs on the moving mouth parts of copepods [5]. By contrast, frogs [6] and basilisk lizards generate a turbulent flow beneath their wide and flat feet (Reynolds numbers 5000-15000) and to run on water, a basilisk lizard must maintain a pocket of air above its feet [7,8]. Pygmy mole crickets and copepods therefore exploit the viscosity of water, basilisk lizards its mass, and pond skater insects [9], and fisher spiders [10] its surface tension.…”
Section: Pygmy Mole Crickets Jump From Water Malcolm Burrows* and Grementioning
confidence: 99%
“…The generation of thrust is possible because of the viscosity of water relative to body size; the paddles and spurs act in a similar way to the smaller hairs on the moving mouth parts of copepods [5]. By contrast, frogs [6] and basilisk lizards generate a turbulent flow beneath their wide and flat feet (Reynolds numbers 5000-15000) and to run on water, a basilisk lizard must maintain a pocket of air above its feet [7,8]. Pygmy mole crickets and copepods therefore exploit the viscosity of water, basilisk lizards its mass, and pond skater insects [9], and fisher spiders [10] its surface tension.…”
Section: Pygmy Mole Crickets Jump From Water Malcolm Burrows* and Grementioning
confidence: 99%
“…Less celebrated is their impressive swimming ability [5][6][7] which has revealed important mechanisms of fluid propulsion [8][9][10], making frogs ideal models to probe the limits of muscle-powered swimming.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of our knowledge on frog locomotion is based on data for a limited set of derived frogs including ranoids [mostly ranids and bufonids (Calow and Alexander, 1973;Lutz and Rome, 1994;Kamel et al, 1996;Peters et al, 1996;Olson and Marsh, 1998;Gillis and Biewener, 2000;Nauwelaerts and Aerts, 2002;Nauwelaerts and Aerts, 2003;Nauwelaerts and Aerts, 2006;Nauwelaerts et al, 2001;Nauwelaerts et al, 2004;Nauwelaerts et al, 2005a;Nauwelaerts et al, 2005b;Johansson and Lauder, 2004;Stamhuis and Nauwelaerts, 2005)] and highly specialized aquatic pipids (Gal and Blake, 1988;Richards and Biewener, 2007;Richards, 2008;Clemente and Richards, 2013). A comparison of swimming kinematics between the highly specialized aquatic pipids and more generalized terrestrial species showed differences in joint kinematics, indicating differences in the underlying propulsive strategies of swimming across species (Richards, 2010).…”
mentioning
confidence: 99%